2017
DOI: 10.1200/jco.2017.73.4418
|View full text |Cite
|
Sign up to set email alerts
|

SIMPLIFY-1: A Phase III Randomized Trial of Momelotinib Versus Ruxolitinib in Janus Kinase Inhibitor–Naïve Patients With Myelofibrosis

Abstract: Purpose We evaluated the efficacy and safety of momelotinib, a potent and selective Janus kinase 1 and 2 inhibitor (JAKi), compared with ruxolitinib, in JAKi-naïve patients with myelofibrosis. Patients and Methods Patients (N = 432) with high risk or intermediate-2 risk or symptomatic intermediate-1 risk myelofibrosis were randomly assigned to receive 24 weeks of treatment with momelotinib 200 mg once daily or ruxolitinib 20 mg twice a day (or per label), after which all patients could receive open-label momel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
223
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(236 citation statements)
references
References 17 publications
10
223
0
3
Order By: Relevance
“…A number of other JAK inhibitors have been developed, and although some have entered clinical trials in patients with MPN, their development has been delayed by early toxicity issues, or a lack of benefit over ruxolitinib. Firstly, momelotinib, a JAK1/JAK2 inhibitor, showed similar responses to ruxolitinib with respect to reduction in spleen size, but lesser alleviation of constitutional symptoms in phase 3 trials in patients with MF, although momelotinib was associated with a reduced transfusion requirement relative to ruxolitinib [53,54]. Long-term data failed to show a survival benefit of treatment with momelotinib, and demonstrated a high incidence of peripheral neuropathy [55], and studies of momelotinib in PV and ET were discontinued as a result of limited efficacy [56].…”
Section: New Agentsmentioning
confidence: 99%
“…A number of other JAK inhibitors have been developed, and although some have entered clinical trials in patients with MPN, their development has been delayed by early toxicity issues, or a lack of benefit over ruxolitinib. Firstly, momelotinib, a JAK1/JAK2 inhibitor, showed similar responses to ruxolitinib with respect to reduction in spleen size, but lesser alleviation of constitutional symptoms in phase 3 trials in patients with MF, although momelotinib was associated with a reduced transfusion requirement relative to ruxolitinib [53,54]. Long-term data failed to show a survival benefit of treatment with momelotinib, and demonstrated a high incidence of peripheral neuropathy [55], and studies of momelotinib in PV and ET were discontinued as a result of limited efficacy [56].…”
Section: New Agentsmentioning
confidence: 99%
“…13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib. 21 Here, we report the outcome of 218 patients after ruxolitinib.…”
Section: Introductionmentioning
confidence: 99%
“…46 Comparison with ruxolitinib in the SIMPLIFY-1 trial did not show benefits to treatment with momelotinib with regard to spleen size reduction and symptom improvement (spleen response: 26.5% in momelotinib group and 29% of the ruxolitinib group (p=0.011 for non-inferiority); ≥50% reduction in total symptom score: 28.4% for momelotinib vs 42.2% for ruxolitinib [noninferiority not met; p=0.98]). 46,47 Adverse event profiles were comparable for momelotinib, ruxolitinib, and BAT with peripheral neuropathy (in up to 50% of patients) and myelosuppression being the most frequent adverse events seen with momelotinib. 46,48,49 In single-arm studies of mostly treatment-naïve patients, momelotinib achieved clinical/symptom responses in up to 57.6% and spleen responses in 45% of patients, respectively, and no survival benefit compared to risk-matched patients not receiving momelotinib was seen.…”
Section: Other Jak Inhibitors In Clinical Trialsmentioning
confidence: 95%